Assessment of Records Management Storage Practices in Medical Centers: Case Study of Rugarama Hospital. - Akello, Deborah (Kabale University, 2024)
This study focused on evaluating the records management storage practices at Rugarama Hospital. The main objective was to assess the records management storage practices in the hospital's records department. Specifically, the study aimed to: examine the current records storage practices at Rugarama Hospital, identify the challenges faced in records storage, and suggest potential solutions for improving records storage management. The research utilized a case study design with both quantitative and qualitative approaches. Data was collected from 44 participants, including department heads, records section staff, and medical staff at Rugarama Hospital, using self-administered questionnaires and interview guides. Quantitative data were analyzed using Excel to generate frequencies and percentages, while qualitative data were analyzed to identify themes, and results were presented in tables for interpretation. The findings revealed that the primary records storage method at Rugarama Hospital was physical paper-based storage, as indicated by 79.5% of respondents, with 46% stating that records were organized and stored in cabinets. The study also identified limited space as the main challenge in records storage, as noted by 36.4% of respondents. To address this, 34.1% of respondents suggested that reducing clutter to create more space would be an effective solution. In conclusion, Rugarama Hospital primarily used paper-based records storage, faced challenges with limited space, and could benefit from decluttering. The study recommended that the hospital administration should consider redesigning storage areas to optimize space usage. This could involve adopting compact shelving systems, digitizing older records to free up physical space, and decluttering to enhance storage efficiency.